The Russia-Ukraine crisis presents threats to Nigeria’s food security, but potential opportunities for the fertilizer, energy sectors - Balana, Bedru; Andam, Kwaw S.; Amare, Mulubrhan; Adeyanju, Dolapo; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
The current rise in global market prices for major food commodities almost mirrors that of the 2008 food crisis, presenting a worldwide threat to food security. The situation is particularly severe in Africa, where the COVID-19 pandemic and now the Russia-Ukraine crisis have exposed the vulnerability of food systems to major shocks, particularly in countries like Nigeria that rely heavily on imports of major staple foods such as rice and wheat. With global food prices spiking and supplies of wheat, oils, and other items disrupted due to the Russia-Ukraine war, Nigeria faces a number of threats to its already precarious food security. Since over 50% of the foods consumed by Nigerian households come from purchased sources, food price inflation threatens to place many people in a worsening food insecurity situation. In particular, Nigeria’s dependence on wheat imports may lead to high prices and supply problems. At the same time, however, Nigeria’s capacity to produce other key items — in particular, fertilizer and natural gas — may allow it to take advantage of global market disruptions from the crisis. In this post, we examine how wheat supply disruptions and spiking prices caused by the Russia-Ukraine conflict may exacerbate food insecurity in Nigeria, and also explore the country’s potential opportunities in the emerging fertilizer sector and energy industries.